2021
DOI: 10.1016/j.jaut.2021.102730
|View full text |Cite
|
Sign up to set email alerts
|

Short term outcomes of COVID-19 in lupus: Propensity score matched analysis from a nationwide multi-centric research network

Abstract: Objectives To determine the severity and outcome of COVID-19 among individuals with lupus as compared to controls. The secondary objective was to identify the risk association of sex, race, presence of nephritis, and use of various immunomodulators with COVID-19 outcomes. Methods Retrospective data of individuals with lupus with and without COVID-19 between January 2020 to May 2021 was retrieved from the TriNetX. A one-to-one matched COVID-19 positive control was select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
0
25
1
4
Order By: Relevance
“…In addition, we confirmed in one of the largest studies exploring COVID-19 outcomes in patients with rheumatic diseases, that neither SLE, SjS, Sarcoidosis, SSc, IIM, MUCTD BD or SV, individually, were associated with a higher mortality risk. Whilst previous reports have analyzed the impact of SLE or Sarcoidosis with similar conclusions, we identified that some of these diseases, less studied due to their lower prevalence, do not relate to worse COVID-19 outcomes [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 63%
“…In addition, we confirmed in one of the largest studies exploring COVID-19 outcomes in patients with rheumatic diseases, that neither SLE, SjS, Sarcoidosis, SSc, IIM, MUCTD BD or SV, individually, were associated with a higher mortality risk. Whilst previous reports have analyzed the impact of SLE or Sarcoidosis with similar conclusions, we identified that some of these diseases, less studied due to their lower prevalence, do not relate to worse COVID-19 outcomes [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, on primary analysis, the risks for all complications and adverse outcomes were significantly higher in patients with RA [45]. But after propensity matching for age and comorbidities, the risks for adverse outcomes with RA did not differ as compared to non-RA patients except for sepsis and venous thromboembolism [46]. Overall, the increased risk for adverse outcomes in RA is related to age and associated comorbidities, with a specific association of DM with increased risk of infection, hospitalization, and death.…”
Section: Rheumatoid Arthritismentioning
confidence: 88%
“…All three studies have analyzed patients before the availability of COVID-19 vaccines and need to be interpreted accordingly as discussed below [44][45][46].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“… 1 In a large study of over 2000 patients with SLE and COVID-19, lupus patients were more likely to require hospitalisation or mechanical ventilation, have concomitant sepsis or thromboembolic disease (including venous thromboembolism or stroke) than the general population. 2 …”
Section: Introductionmentioning
confidence: 99%